Penerapan Corporate Social Responsibility pada Lembaga Keuangan Berbasis Kearifan Lokal - Ni Wayan Novi Budiasni; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2016)
This study aims to explore and understand the application of CSR based on localwisdom (Tri Hita Karana) in Bali that are applied by the Village Credit Institutions (LPD)and LPD Tibekauh Penglatan Singaraja Gianyar. Implementation of CSR on both LPD werecompared in this study. Each program will be tailored CSR applied to aspects parhyangan,palemahan, pawongan in the Tri Hita Karana.This study will address issues related to the implementation of CSR by LPD based onlocal wisdom, LPD social fund allocation, and allocation of social funds in terms of financialperformance LPD. There are three questions are formulated.This study uses a qualitative method. The technique of collecting data using interviews,observation, documentation, and deployment of an open questionnaire to customers or thepublic. Informants determined by purposive sampling. Use interactive data analysistechniques. Technique authenticity of data by researchers to test the credibility andtriangulation. Data used in the form of primary and secondary data.Implementation of CSR in the LPD can be said to be based Tri Hita Karana. However,CSR program in Singaraja Penglatan LPD more active than the LPD Tibekauh Gianyar.LPD Tibekauh Gianyar co-own shortcomings in aspects palemahan. This is because the CSRprogram LPD Tibekauh on aspects palemahan not comprehensive.CSR is applied LPD Penglatan Singaraja and Tibekauh Gianyar can be said to containaspects of tri hita karana (parhyangan, palemahan, pawongan). The program is applicable toalmost the same, except that the amount of applied programs tailored to ability. CSR isapplied adapted to the needs of the surrounding environment so that CSR is implementedeffectively. The allocation of social funds have been set in gubernatorial. Bali Provincial No.11 Year 2013 concerning LPD as much as 5%, and the village development fund 20% of itsnet profit in the year-end LPD. The higher net income LPD, the higher allocation of funds ofsocial and rural development.CSR shall be implemented by LPD. The goal is improve the lives of the surroundingenvironment. So that goal is reached, the program is designed to be effective and perceivedby the public contribution. So the LPD need to create an education program in which ifappropriately carried out and fill the needs of the community. CSR mandatory because LPDownedPakraman and utilize the resources around.Future studies are expected to enhance this work by including a component of financialstatements that reflect social activities menyuluruh LPD and assess the financial aspectsrelated to the allocation of funds LPD social and rural development.Keywords: Corporate Social Responsibility, Tri Hita Karana, Net Income